Recent advances in electrochemical sensors and biosensors for monitoring drugs and metabolites in pharmaceutical and biological samples - Charaf Laghlimi; Abdelaziz Moutcine; Abdelilah Chtaini; Jalal Isaad; Adil Soufi; Younes Ziat; Hassan Amhamdi; Hamza Belkhanchi (International Association of Physical Chemists (IAPC), 2023)
Various applications of electrochemical sensors and biosensors have been reported in many fields. These include pharmaceuticals, drug detection, cancer detection, and analysis of toxic elements in tap water. Electrochemical sensors are characterised by their low cost, ease of manufacture, rapid analysis, small size and ability to detect multiple elements simultaneously. They also allow the reaction mechanisms of analytes, such as drugs, to be taken into account, giving a first indication of their fate in the body or their pharmaceutical preparation. Several materials are used in the construction of sensors, such as graphene, fullerene, carbon nanotubes, carbon graphite, glassy carbon, carbon clay, graphene oxide, reduced graphene oxide, and metals. This review covers the most recent progress in electrochemical sensors used to analyze drugs and metabolites in pharmaceutical and biological samples. We have highlighted carbon paste electrodes (CPE), glassy carbon electrodes (GCE), screen-printed carbon electrodes (SPCE) and reduced graphene oxide electrodes (rGOE). The sensitivity and analysis speed of electrochemical sensors can be improved by modifying them with conductive materials. Different materials used for modification have been reported and demonstrated, such as molecularly imprinted polymers, multiwalled carbon nanotubes, fullerene (C60), iron(III) nanoparticles (Fe3O4NP), and CuO micro-fragments (CuO MF). Manufacturing strategies and the detection limit of each sensor have been reported.